Political campaign activities in the 1990 general election / Abdullah @ Kassim Mohamad - Mohamad, Abdullah @ Kassim (Faculty of Communication and Media Studies (FCMS), 1994)
The general election in October 1990 gave a great opportunity to a group of researchers comprising of students from the school of mass communication, ITM to undertake a study on the political campaign activities. In their studies, they tried to identify the approaches use by all parties involved in the campaign. Important issues in the main agenda in the campaign were detected. Useful data and issues brought up by each speakers were gathered and interviews were also conducted with the audience. From they are able to measure the audience ability to understand the issues discussed.